DIAGNOSA PENYAKIT SARAF MANUSIA DENGAN METODE FORWARD CHAINING DALAM SISTEM PAKAR - Windi Afridah Sari; Adi Prijuna Lubis; Abdul Karim Syahputra (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Neurological disease is a disease that attacks the nervous system in the human body. Neurological consist of millions of nerve fibers that have parts of nerve cells that are interconnected and function as growth, brain development, feeling sensation, perception, thoughts and emotions, as well as movement and balance in the human body. Neurological disease is caused by impact of hard objects, exposure to chemicals, viruses or bacteria and inflammation caused by the regeneration of nerve cells themselves. Most people do not know for sure and underestimate the symptoms of neurological disease. An expert system is a knowledge system that provides information or solutions based on the knowledge of an expert to produce information and solutions. The method used in this study is the Forward Chaining method. The forward search process begins with the premise or input information (IF) then leads to conclusions or derivative information (THEN) such as, IF (Input Information) THEN (conclusion) in the form of data, evidence, findings or symptoms. While conclusions can be in the form of goals, hypotheses, explanations or diagnoses. In this study, an expert system will be designed that is used to diagnose human neurological diseases using the Forward Chaining method as a tool system or provide diagnostic results to users based on symptoms and know the types of neurological diseases and know how to treat them.